Nothing special in the specialist? Draft genome sequence of Cryomyces antarcticus, the most extremophilic fungus from Antarctica. - Katja Sterflinger; Ksenija Lopandic; Ram Vinay Pandey; Barbara Blasi; Albert Kriegner (PLoS ONE)
The draft genome of the Antarctic endemic fungus Cryomyces antarcticus is presented. This rock inhabiting, microcolonial fungus is extremely stress tolerant and it is a model organism for exobiology and studies on stress resistance in Eukaryots. Since this fungus is a specialist in the most extreme environment of the Earth, the analysis of its genome is of important value for the understanding of fungal genome evolution and stress adaptation. A comparison with Neurospora crassa as well as with other microcolonial fungi shows that the fungus has a genome size of 24 Mbp, which is the average in the fungal kingdom. Although sexual reproduction was never observed in this fungus, 34 mating genes are present with protein homologs in the classes Eurotiomycetes, Sordariomycetes and Dothideomycetes. The first analysis of the draft genome did not reveal any significant deviations of this genome from comparative species and mesophilic hyphomycetes.